Македонскиот војник и петокраката 1941-1992 - Macedonian Soldier and the Red Five-pointed Star 1941-1992 - Robert Mitevski (Македонски хералд - Macedonian Herald, 2020)
The five-pointed star in red as an anti-fascist symbol persisted on the hat of the Macedonian soldier from the beginning of the Second World War until the end of 1992. De facto, the Army of the Republic of Macedonia was the last military force in Europe that proudly carried it as a sign of affiliation in the turbulent period of gaining independence and the months that followed. The great diversity in type and number (over a hundred variations by periods, ranks, and manufacturers) in this text are systematized, dated, and identified represented by dimensions and weight.A photo-tabular overview of the five-pointed star in the periods from 1951 to 1992 is given of Officers, non-commissioned officers and soldiers for hats and visor hats, as well as overlapping military with security cords and modern copies.